Groups process and practice - Corey, Marianne Schneider 1942-; Corey, Gerald; Corey, Cindy (Cengage Learning, 2018)
"This book outlines the basic issues and key concepts of group process and shows how group leaders can apply these concepts in working with a variety of groups. In many ways this is a 'how-to' book, but it is also a book about the 'why' of group leadership... this tenth edition...contains many subtle changes in our discussion of the topics within ech chapter, and many chapters have undergone considerable revision with new material added."--page xvii.